Provirus reactivation is impaired in HIV-1 infected individuals on treatment with dasatinib and antiretroviral therapy - Vigon, Lorena; Martínez-Roman, Paula; Rodríguez-Mora, Sara; Torres, Montserrat; Puertas, María C.; Mateos, Elena; Salgado, María; Navarro, Antonio; Sánchez-Conde, Matilde; Ambrosioni, Juan; Cervero, Miguel; Wyen, Christoph; et al. (Elsevier, 2021)
The latent viral reservoir formed by HIV-1, mainly in CD4 + T cells, is responsible for the failure of antiretroviral therapy (ART) to achieve a complete elimination of the virus in infected individuals. We previously determined that CD4 + T cells from individuals with chronic myeloid leukemia (CML) on treatment with dasatinib are resistant to HIV-1 infection ex vivo. The main mechanism for this antiviral effect is the preservation of SAMHD1 activity. In this study, we aimed to evaluate the impact of dasatinib on the viral reservoir of HIV-infected individuals with CML who were on simultaneous treatment with ART and dasatinib. Due to the low estimated incidence of HIV-1 infection and CML (1:65,000), three male individuals were recruited in Spain and Germany. These individuals had been on treatment with standard ART and dasatinib for median 1.3 years (IQR 1.3¿5.3 years). Reservoir size and composition in PBMCs from these individuals was analyzed in comparison with HIV-infected individuals on triple ART regimen and undetectable viremia. The frequency of latently infected cells was reduced more than 5-fold in these individuals. The reactivation of proviruses from these cells was reduced more than 4-fold and, upon activation, SAMHD1 phosphorylation was reduced 40-fold. Plasma levels of the homeostatic cytokine IL-7 and CD4 effector subpopulations TEM and TEMRA in peripheral blood were also reduced. Therefore, treatment of HIV-infected individuals with dasatinib as adjuvant of ART could disturb the reservoir reactivation and reseeding, which might have a beneficial impact to reduce its size.